Collaboration of RSA Algorithm Using EM2B Key with Word Auto Key Encryption Cryptography Method in Encryption of SQL Plaintext Database - Purba, Elwin Yunith; Efendi, Syahril; Sirait, Pahala; Sihombing, Poltak (Journal of physics. Conference series, 2019)
RSA algorithm is a modern cryptographic algorithm and is often used for data security, and until now no one has been able to solve it. This algorithm uses two keys, public key and private key, the degree of difficulty of this algorithm lies in the factorization of large prime numbers. EM2B key algorithm function is to change the primary key become a new key into ASCII characters. This algorithm has the increament key algorithm function to change the length of the key characters are same as the plaintext. The Wake method is a stream cipher algorithm uses a 128 bit key and a 256 X 32 bit table. The strength of the RSA algorithm is the bit length used, and the strength of the WAKE method also lies in the bit length used and many rotation that occur. While the strength of the EM2B key algorithm lies in the increament key. After testing, the combination of three alogritmas consists of the RSA algorithm using the EM2B key and WAKE method and a combination of two algorithms with WAKE method using the EM2B key, the encryption results are better and safer than using only one WAKE algorithm.